1991
DOI: 10.1093/ije/20.1.151
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Body Mass and Fat Distribution with Sex Hormone Concentrations in Postmenopausal Women

Abstract: The associations of body mass and body fat distribution, as measured by waist-to-hip circumference ratio, with serum concentrations of sex hormones and sex hormone binding globulin were examined in 88 postmenopausal women. Body mass index (BMI) was significantly and negatively associated with sex hormone binding globulin (SHBG) (r = -0.41), luteinizing hormone (LH) (r = -0.40) and follicle stimulating hormone (FSH) (r = -0.38) and was also significantly positively associated with both total and free oestradiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
101
3
1

Year Published

1992
1992
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 208 publications
(112 citation statements)
references
References 0 publications
7
101
3
1
Order By: Relevance
“…Furthermore, C-peptide and IGF-I correlated independently with levels of sex-steroid hormones and SHBG. The relationships of adiposity with C-peptide, SHBG and free sex-steroid hormones in our study confirm results of previous studies [12,18,[20][21][22][23][24][25]. High levels of insulin, for which C-peptide is a marker, have been associated with excess weight and inhibit SHBG production in the liver [7,26].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Furthermore, C-peptide and IGF-I correlated independently with levels of sex-steroid hormones and SHBG. The relationships of adiposity with C-peptide, SHBG and free sex-steroid hormones in our study confirm results of previous studies [12,18,[20][21][22][23][24][25]. High levels of insulin, for which C-peptide is a marker, have been associated with excess weight and inhibit SHBG production in the liver [7,26].…”
Section: Discussionsupporting
confidence: 90%
“…For total estrogen measurements, BMI and waist circumference were directly correlated with estrone and estradiol only in postmenopausal women, as observed in previous studies [12,22,23,39]. In premenopausal women, results of former studies have been somewhat contradictory, but in general no association was observed between BMI and estrogens [20,21,33,40], as in our study.…”
Section: Bmi Waist Circumference and Sex-steroid Hormone Concentrationssupporting
confidence: 82%
See 1 more Smart Citation
“…Significant trends of increasing risk with increasing levels of all hormones were observed in matched analyses not adjusted for additional factors (model a). As body mass index is a determinant of circulating oestrogen levels (Vermeulen and Verdonck, 1979;Poortman et al, 1981;Kaye et al, 1991) and therefore on the same causal pathway as oestrogens, we present adjusted analyses both including and excluding this variable (plus height, as recommended by Michels et al, 1998). Adjusting for age at menarche, parity, age at first birth, family history of breast cancer, and history of breast biopsy, one variable at a time (data not shown) or simultaneously (Table 3, model b) did not materially affect the ORs.…”
Section: Resultsmentioning
confidence: 99%
“…That excess adiposity, particularly in the upper body, is correlated with increased levels of bioavailable estrogen is well known. 102 Mechanisms point to associations between obesity and/or upper body adiposity with decreased levels of sex hormone bonding globulin, 103,104 hyperinsulinemia, and correspondingly higher levels of insulin-like growth factor type I. 105,106 In studies that included large numbers of African American women, obesity has also been shown to be associated with larger tumors, positive lymph nodes, and later stage at diagnosis.…”
Section: Obesitymentioning
confidence: 99%